Calcium phosphate accelerated setting time of the o-ethoxybenzoic acide (EBA) temporary cement - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2003)
The temporary crowns and bridges are usually cemented into place with a zinc oxide-eugenol composition. ZOE cements reduce the efficacy of dentine-bonding systems. Their disadvantages, include low strength and abration resistance, high solubility, and fast disintegration in oral fluids, and minor anticarrogenic action. However EBA systems have higher strength, lower solubility, and does not inhibit vinyl polymerization. They have very good correlation with composite materials and tissue. Calcium phosphate has properties resembling the main inorganic phase of hard tissues such as enamel, dentine. Properties such as setting time or strength of the cements appear to be influenced markedly by the addition of calcium phosphate In this study 5% calcium phosphate was added to classical EBA formulation. New EBA cement is stronger and has longer working time than the ordinary EBA formulation.
Keywords: o-ethoxybenzoic acid; EBA cement; noneugenol cement; zinc oxide-eugenol cement; EUGENOL